Isolamento e caracterização de bactérias diazotróficas em arroz silvestre (Oriza glumaepatula Steud) no estado de Roraima - Silva, Luana Mesquita da (2010)
Species of wild rice are colonized by diazotrophic bacterias, however, little is known about the colonization in Oryza glumaepatula (Steud). This study aimed isolate and characterize diazotrophic bacterias of the wild rice from forest and cerrado areas in the Amazon biome. Samples of wild plants were collected for bacterial isolation, and semi- solid medium was used to assay the pellicles formation by the bacterias. Later, the nifH gene was also amplified by PCR using the primer set PolF/PolR and the bacterias, each ones were positive, characterized through Box-PCR, solubilization of calcium phosphate and production of indol acetic acid (AIA). Thirty eight bacterias, around 4% of the total, formed pellicles and also presented nifH gene amplification. A incidência de bactérias diazotróficas foi semelhante entre as áreas, porém maior número foi isolado na parte aérea das plantas. Além disso, mais de 30% das bactérias diazotróficas apresentaram produção de AIA e/ou solubilização de fosfato, sendo a maior concentração na parte aérea das plantas do cerrado. Nessa área ocorre maior diversidade genotípica de bactérias diazotrófica associadas ao arroz silvestre e maior número destas bactérias capazes de solubilizar fosfato de Ca e produzir AIA. The incidence of diazotrophic bacterias was similar between the areas, however, higher number was isolated from the aerial part of the plants. Furthermore, more than 30% of the diazotrophic bacterias produced AIA and/or solubilized phosphate, and the largest concentration of these bacteria was isolate in the aerial part of the plants from cerrado. In this area happens higher genotypic diversity of diazotrophic bacterias associated to the wild rice and also the larger number of these bacterias is capable producing AIA and solubilizing phosphate.